NUMERICAL STUDY OF MIXED CONVECTION IN A HORIZONTAL CHANNEL FILLED WITH A FLUID-SATURATED POROUS MEDIUM - Ozgen, Filiz; Varol, Yasin; Öztop, Hakan Fehmi Fehmi (Turkish Soc Thermal Sciences Technology, 2013)
In this study, mixed convection heat transfer has been investigated in a horizontal plate filled with porous media. Mixed convection flow over a heated plate in a saturated porous medium is widely used due to a large number of technical applications, such as fluid flow in geothermal reservoirs, separation processes in chemical industries, storage of radioactive nuclear waste materials, and cooling. Governing equations, written in dimensionless form, have been solved for a range of values of the governing parameters using the finite element method. In the present study, results were presented with streamlines, isotherms, local and mean Nusselt numbers. According to the obtained data, Rayleigh number and Peclet number were important parameters on flow and temperature fields.
Keywords: Mixed convection; Channel; Porous medium